Analysis of Implementation of Clean and Healthy Lifestyle Behavior (PHBS) During the COVID-19 Pandemic at Islamic Boarding School X, Malang City - Endang Sri Redjeki; Windi Chusniah Rachmawati; Tiara Dhea Yurisdian (Universitas Negeri Malang, 2023)
Clean and Healthy Lifestyle Behavour (PHBS) is a set of behaviors that are practiced on the basis of awareness as learning outcomes that make a person, a family, a group, and community able to help themselves in the health sector and play an active role in realizing public health. It is still an effort to cultivate clean and healthy living behavior in Islamic boarding schools, as well as to recognize problems and levels of their health, and to be able to overcome, maintain, improve and protect their own health. This study aims to determine and analyze the implementation of PHBS students in Islamic boarding schools during the COVID-19 pandemic. This research was conducted in 151 Islamic boarding school students using a questionnaire given to every student who was willing to be a respondent.